Digital video broadcasting : terrestrial application development - Ling, Eldine Yu Xian. (2009)
Digital Video Broadcasting (DVB) is defined as the internationally accepted standards for digital broadcast and has been the key solution to problems and limitations faced by analog broadcasting. DVB systems distribute data using a variety of methods most commonly of which include: satellite (DVB-S, DVB-S2), cable (DVB-C), terrestrial television (DVB-T) and terrestrial television for handhelds (DVB-H). With the tremendous advancement of DVB-T technology, the desire to develop DVB-T application on embedded system platform marks the new beginning of Digital Media era. This project aims to develop a real time system to improve on live media streaming through a DVB-T tuner and the trimedia platform, via software decoding. It also involves the optimization of the software modules to improve the efficiency of decoding High Definition Televeision (HDTV). This is a continuation project which has been ongoing for two years, where the Philips Tuner will be replaced by a USB DVB-T Receiver, to be connected to the Nexperia Processor PNX 1500 to receive real time transport stream data and finally demultiplexed into audio and video streams. This project has provided a very good learning experience for the student. It not only has allowed the student to gain a vast knowledge from the standards of MPEG 2. But also it has given a chance for the student to learn a lot more with regards to developing embedded system applications.